Psychological distress and family support mediate suicidal ideation in adolescents diagnosed with cancer: A literature review - Yunike, Yunike; Winta, Mulya Virgonita Iswindari; Pratiwi, Margaretha Maria Shinta (Science Midwifery, 2024)
This study aims to review the literature regarding suicidal ideation in adolescents with cancer. Adolescents with a cancer diagnosis face significant physical and emotional challenges, which may increase the risk of suicidal ideation. This study examines various factors that contribute to this increased risk, including the psychological impact of a cancer diagnosis, and family support. The research methodology involved searching and critical analysis of journal articles, books, and reliable sources published in the last ten years and using relevant keywords including 'suicidal ideation in adolescents' 'psychology of adolescents with cancer,' and 'adolescent developmental tasks' and 'adolescents' developmental tasks'. family support in peer reviewed journals resulting in ten articles being obtained. The results of this study show that teenagers with cancer are at higher risk of experiencing suicidal ideation compared to healthy teenagers. Family support significantly reduces the risk. Practical implications of these findings include the development of more integrated psychological support programs in adolescent cancer care, as well as training for health professionals in recognizing and treating signs of suicidal ideation. This study suggests the need for further research to explore the effectiveness of different interventions in different contexts and identify the most effective prevention strategies.